PENGARUH MANAJEMEN K3, PERILAKU TENAGA KERJA DAN ALAT PELINDUNG DIRI TERHADAP KESELAMATAN TENAGA KERJA BONGKAR MUAT DI TERMINAL NILAM TANJUNG PERAK SURABAYA - Andar Sri Sumantri (STEKOM PRESS, 2020)
The safety of loading and unloading workers is influenced by several factors including K3 Management, Workforce Behavior and Personal Protective Equipment. Of the three, they have an important role in improving the safety of loading and unloading workers with satisfactory results. The purpose of this study was to determine whether there is an influence of K3 Management, Workforce Behavior and Personal Protective Equipment on the Safety of Loading and Unloading Workers at Nilam Terminal PT. Pelabuhan Indonesia III (Persero) Tanjung Perak SurabayaBranch The results of the analysis with statistical tools SPSS V.21 program obtained multiple linear regression equation Y= -1,150 +0,350 X1 + 0,408 X2 +0,318 X3 + . The results of the multiple linear equations show that there is a positive and significant influence between K3 Management on the Safety of Loading and Unloading Workers (t count 4,092 > t table of 1.99085), Labor behavior on the Safety of Loading and Unloading Workers (t count 3.251 > t table of 1.99085), Personal protective equipment against loading and unloading worker safety (t count 2.944 > t table 1.99085), individually K3 Management, Workforce Behavior and Protective Equipment affect the safety of loading and unloading workers.